(untitled) (Biological Sciences - PJSIR, 2005)
Viscosities of poly(vinyl alcohol) in aqueous-methanol system (10% to 50%, v/v) and aqueous-butanol system (1% to 5%, v/v) were measured at different temperatures (25 to 45 ± 0.1 °C) with different concentrations of poly(vinyl alcohol) ranging between 3.0 to 9.0 g/l. Solute-solvent interactions were found affected by changes in the compositions of solvents and the temperature. Various thermodynamic parameters were determined by the change in viscosity data as a function of temperature. It was observed that the free energy change of activation (DG*) increased regularly as the concentration of poly(vinyl alcohol) increased, but the effect with rise in temperature was uncertain. However, the values of DG* of poly(vinyl alcohol) in aqueous-butanol were found to be higher than aqueous-methanol, which showed that associations were higher in aqueous-methanol, as compared with aqueous-butanol solutions. The values of entropy change of activation (DS*) of viscous flow increased with increase in the concentration of the polymer. The high negative values of entropy change of activation (DS*) showed that the solution of the polymer was more ordered in initial state than the activated one.